MENGATASI RENDAHNYA KEMANDIRIAN BELAJAR PESERTA DIDIK MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK SELF CONTROL - Amalia Widyastuti; Edris Zamroni; Agung Slamet Kusmanto (Universitas Muria Kudus, 2022)
The objectives of this study are 1. The application of group guidance services with self-control techniques can overcome the low learning independence of students at SMKN 3 PATI. 2. Obtain an increase in the effectiveness of students' learning independence through group guidance services with self control techniques.Based on the results of this study, there is an increase in the self-control technique group guidance service at SMK Negeri 3 Pati. This can be seen from the results of the pre-cycle scores of students obtaining an average of 75 with the category of sometimes (KD), then in the first cycle the average number of 122 with the frequent category (SR), and in the second cycle the average number of - an average of 142 with the category always (SL).The conclusion of this research is that the self-control technique group guidance service increased by 15 scores from cycle I to cycle II. Thus overcoming the low learning independence of students can be improved through self-control technique group guidance services.